Detection of SEA-type α-thalassemia in embryo biopsies by digital PCR - Ta-Hsien Lee; Ya-Chiung Hsu; Chia Lin Chang (Elsevier, 2017)
Objective: Accurate and efficient pre-implantation genetic diagnosis (PGD) based on the analysis of single or oligo-cells is needed for timely identification of embryos that are affected by deleterious genetic traits in in vitro fertilization (IVF) clinics. Polymerase chain reaction (PCR) is the backbone of modern genetic diagnoses, and a spectrum of PCR-based techniques have been used to detect various thalassemia mutations in prenatal diagnosis (PND) and PGD. Among thalassemias, SEA-type α-thalassemia is the most common variety found in Asia, and can lead to Bart's hydrops fetalis and serious maternal complications. Materials and methods: To formulate an efficient digital PCR for clinical diagnosis of SEA-type α-thalassemia in cultured embryos, we conducted a pilot study to detect the α-globin and SEA-type deletion alleles in blastomere biopsies with a highly sensitive microfluidics-based digital PCR method. Genomic DNA from embryo biopsy samples were extracted, and crude DNA extracts were first amplified by a conventional PCR procedure followed by a nested PCR reaction with primers and probes that are designed for digital PCR amplification. Results: Analysis of microfluidics-based PCR reactions showed that robust signals for normal α-globin and SEA-type deletion alleles, together with an internal control gene, can be routinely generated using crude embryo biopsies after a 106-fold dilution of primary PCR products. Conclusion: The SEA-type deletion in cultured embryos can be sensitively diagnosed with the digital PCR procedure in clinics. The adoption of this robust PGD method could prevent the implantation of IVF embryos that are destined to develop Bart's hydrops fetalis in a timely manner. The results also help inform future development of a standard digital PCR procedure for cost-effective PGD of α-thalassemia in a standard IVF clinic.